Figurative language and Symbolism Manifested in Bukusu Cultural Songs and Proverbs - Aggrey Wafula Watulo (Sociometry Journal of Social Science, Art and Humanity, 2021)
The paper investigates the place of song, dance and proverbs as manifested in selected cultural practices of Bukusu community. Song, dance and proverbs are notoriously utilized with each having roots and a focus to a specific event. The objective of the study include the role, occasion and function of such markers of culture that have been utilized during crowded festivities despite the Covid 19 pandemic. In light of this, the proposition made is that language and culture have a close interplay and promote social ties hence maintaining societal cultural festivities like marriage, burial, circumcision just to list a few. The trajectory created in such rich cultural festivities has been thwarted by the pandemic. Amid the pandemic, such manifestation of cultural rights are promoted either publicly or in hideout in a number of homes to ensure that culture is passed from one generation to the other. The argument raised in view of this, is one that ensures that culture is promoted through linguistic ability, oratory skills, song, music and dance with an aim of creating a cohesive society hence building a rich cultural society. Culture is communicated through literary and linguistic tools such as proverbs, song, symbolism and propaganda. Coupled with a myriad of cultural activities among the community the paper forms a base for an analysis of selected festivities that have gained prominence amid the ravages of the pandemic. The study adopts convenience sampling technique to identify subjects. Data was collected through participant observation and focus group discussion of the cultural activities within Bungoma County. The participants were drawn from notorious villages that have continuously promoted the cultural festivities through crowds despite the escalating numbers of Covid 19 victims. The data will be analyzed descriptively.